Cost-effectiviness analysis of sequential studies in the diagnosis of thyroid carcinoma. - Delgado, Bolívar; Yametti, Luis (Cirugía del Uruguay, 1985)
On the basis of the analysis of a series of 221 thyroid nodules examinad through cytology, gammagraphy and echography, a series of plans of sequenlial study based on the cost-effectiviness point of view are discussed, arriving to the conslusion that the echographycytology plan is !he best suited for local condilion.